It is an expression that can be simplified to -8t-38
-8t = -152 t = 19
15t = 17 + 8t -24 15t - 8t = 17 - 24 7t = -7 t = -1
The "answer" is the number that can be put in place of 't' and makes [ 8t-3=9 ]a true statement.Here's how to find out what it is:8t - 3 = 9Add 3 to each side of the equation:8t = 12Divide each side by 8:t = 1.5
Since 1 ton is equal to 2,000 lb, 8T is equal to 16,000 lb.
8t equals -42 = -34
It is an expression that can be simplified to -8t-38
-8t = -152 t = 19
6 + 11x - 60 =6 - 60 + 11x = -54 + 11x = 11x -54
108
11x
Radius = 8T/(2*pi) = 4T/pi
15t = 17 + 8t -24 15t - 8t = 17 - 24 7t = -7 t = -1
1 + 11x =1 + 11x (this is the simplest solution you can make with available information)
-11x-27=-49 11x+27=49 11x=22 x=2
If you mean 8t+3-t then it is 7t+3 simplified
The "answer" is the number that can be put in place of 't' and makes [ 8t-3=9 ]a true statement.Here's how to find out what it is:8t - 3 = 9Add 3 to each side of the equation:8t = 12Divide each side by 8:t = 1.5